Organic Non‐Wettable Superhydrophobic Fullerite Films (Adv. Mater. 32/2021). Issue 32 (12th August 2021) - Saran, Rinku; Fox, David; Zhai, Lei; Chanda, Debashis
Abstract : Superhydrophobic Surfaces In article number 2102108, Debashis Chanda and co‐workers report organic superhydrophobic surfaces created using colloidal gels of fullerite C60 and C70 . Non‐wettable superhydrophobic films and coatings developed using such semiconducting photosensitizer materials can be exploited in many applications. Furthermore, fullerite films are superaerophilic in an aqueous environment and can stay dry for up to 3 h even at a water depth of 60 cm.